Padronização da técnica de neutralização para quantificação de anticorpos dirigidos contra poliovírus empregando vírus vacinais - Lima, Elaine dos Santos [UNIFESP] (2010)
Even after many decades of efforts to eradicate poliomyelitis this disease is still endemic in some Asian and African countries, representing a threat to all other countries due to international travels. Recently new measures to control viral stocks of poliovirus have been proposed to the health community. Among these the use of wild strains of polio in testing can compromise WHOs aim of absolute poliomyelitis virus eradication. The present study proposes to change the present methodology for one adapted test using vaccine viruses. For this, we used the oral vaccine Sabin and HEp-2 neutralization methodology. We tested 64 samples from patients sera previously titrated antibodies from wild poliovirus strains, considered the gold standard. Results of neutralization with vaccine strains were compared and the parameters were calculated as sensitivity, specificity, prevalence, accuracy, positive predictive value and negative predictive value for the three viral serotypes. Results showed a very close approximation between the results with the vaccine strain and the gold standard. We conclude that this evaluation demonstrates a good performance of the alternative diagnostic procedure, confirmed the immune status of the patients, and provides a great alternative to replace the wild type strain. Thus, we minimize the risks in laboratory procedures, to continue to perform the serological diagnosis of polio, especially in immunocompromised patients and transplant recipients.